The effect of interpersonal communication, facilities and application-based registration on patient satisfaction with service quality as an intervening variable in the outpatient row RSUD Raja Ahmad Tabib Riau Island Province - Herlina, Fetty; Rumengan, Angelina E.; Indrawan, Mohamad Gita (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: The purpose of this study was to analyze the effect of interpersonal communication, facilities, and ease of application-based registration on patient satisfaction with service quality as an intervening variable in the Outpatient Hospital Raja Ahmad Tabib Riau Islands Province. Research methodology: The research design used in this study was quantitative research with an associative type of research in the form of a causal relationship. The population in this study were outpatients who registered using the application totaling 5,818 people. The sample size was determined using the Slovin formula to obtain a sample size of 374 people. The data collection technique in this study was a Likert scale questionnaire, with instruments in the form of questionnaire sheets and Google Forms. The data analysis technique used in this study used the partial least squares (PLS) approach assisted by SmartPLS. Results: The results showed that direct interpersonal communication, facilities, and ease of application-based registration had a significant effect on patient satisfaction in the outpatient department of Raja Ahmad Tabib Hospital, Riau Island Province. Conclusions: Patient satisfaction is influenced by interpersonal communication, facilities, and application-based registration, with service quality acting as a key mediator to enhance overall service experience. Limitations: This study was conducted in a single hospital and limited to patients using application-based registration, thus reducing the generalizability of the findings. Future research should involve more hospitals and broader variables to gain deeper insights. Contribution: This research provides empirical evidence on the critical role of service quality as an intervening variable, offering practical insights for hospital management in improving digital health services and interpersonal interactions to increase patient satisfaction.